A possible reason for non-proportionality of response in NaI:Tl and CsI:Tl scintillation crystals - Kudin, A.M.; Grinyov, B.V.; Gres', V.Yu.; Mitichkin, A.I. (Functional Materials, 2006)
It is known that the light yield L is not proportional to energy Е for many scintillation materials under excitation by external γ-rays. In contrast, L is proportional to Е for internal radiation sources. In this work, it has been shown that this contradiction can be eliminated if the non-proportionality is considered as a total result caused by two effects. First, the scintillation duration is shortened as the photon energy decreases, that results in increasing measured L/Е value at fixed signal formation time. Second, the presence of dead layer results in the luminescence quenching near the crystal surface. In this concept, the response non-proportionality is considered as axial inhomogeneity of the scintillation efficiency depending on the radiation penetration depth Н. It has been shown that the valley in L/Е vs Е dependence near the K-edge of iodine absorption (the jump-like Н changing almost by ten times) disappears on the L/Е vs Н one.